2015
DOI: 10.1021/acs.iecr.5b01268
|View full text |Cite
|
Sign up to set email alerts
|

On Mixing and Segregation: From Fluids and Maps to Granular Solids and Advection–Diffusion Systems

Abstract: In fluids, diffusive transport and fluid parameters are determined by the thermally driven movement of molecules, whereas in granular media, thermal effects play no role in transport. Despite this fundamental difference, mixing in fluids and mixing and segregation in granular solids share many similarities. The advection−diffusion equation formalism unites the two systems and can be used in both cases to predict and understand how and when mixing occurs, through the use of strategic simplifications. We illustr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Note that Eq. predicts that the steady‐state degree of segregation, as characterized, for example, by both the thickness of the pure layers ( c i near 0 and near 1) and the sharpness of the change in concentration between the layers, is insensitive to the shear rate, since both D and w p , i are linear in trueγ˙ . Note also that the steady‐state degree of segregation predicted by Eq.…”
Section: Continuum Modeling Of Confined Flowsmentioning
confidence: 95%
See 1 more Smart Citation
“…Note that Eq. predicts that the steady‐state degree of segregation, as characterized, for example, by both the thickness of the pure layers ( c i near 0 and near 1) and the sharpness of the change in concentration between the layers, is insensitive to the shear rate, since both D and w p , i are linear in trueγ˙ . Note also that the steady‐state degree of segregation predicted by Eq.…”
Section: Continuum Modeling Of Confined Flowsmentioning
confidence: 95%
“…are zero, and the right‐hand side depends only on the second derivative in y . The resulting ordinary differential equation has a solution for the predicted depthwise concentration profiles with the simple form: ci()yfalse˜=11+Aetruey˜/λ, where λ=CDdfalse¯2/()Sh is a nondimensional ratio of segregation to diffusive time scales, truey˜=y/h, C D = 0.042 is the leading coefficient for diffusion described in Figure , S is the segregation coefficient in the segregation velocity equation, h is the height of the shear cell, and A = e 1/(2 λ ) is an integration constant for equal volume mixtures that satisfies the condition 01ci()yfalse˜dtruey˜=0.5. This analytic solution is valid for constant diffusion and segregation coefficients, but Eq.…”
Section: Continuum Modeling Of Confined Flowsmentioning
confidence: 99%
“…To do so, we apply a form of a continuum model that has been successfully applied to quantitatively predict bidisperse size segregation of spherical particles in different geometries [45][46][47][48] as well as bidisperse density segregation 49 and multiand polydisperse size segregation. 50 This continuum segregation model has the general form…”
Section: Introductionmentioning
confidence: 99%
“…To do so, we apply a form of a continuum model that has been successfully applied to quantitatively predict bidisperse size segregation of spherical particles in different geometries as well as bidisperse density segregation and multi‐ and polydisperse size segregation . This continuum segregation model has the general form cit+true(ucitrue)+ztrue(ws,icitrue)true(Dcitrue)=0, where c i is the concentration of species i ( l for long and s for short) such that c i = f i / f , where f i is the local volume fraction of species i , and f is the total volume fraction for all species.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative is to use continuum models to describe the segregation process. Previous research has shown that a continuum model approach can accurately predict segregation in flows of glass-like, frictional particles in multiple geometries, including bounded heaps [5,12,19,20], chutes [31,32,33], cylindrical tumblers [32,34], and planar shear cells [35].…”
Section: Continuum Model For Segregationmentioning
confidence: 99%